Предмет: Алгебра,
автор: Tobi111
методом подстановки: 4x+y=3 6x-2y=1
Ответы
Автор ответа:
0
4х+у=3 из первого ур-я выразим у у=3-4х теперь подставим зна-
6х-2у=1 6х-2у=1 чение у во 2 ур-е
у=3-4х х=0,5 х=0,5
6х-2(3-4х)=1 у=3-4*0,5 у=1
6х-6+8х=1
14х=7
х=0,5
6х-2у=1 6х-2у=1 чение у во 2 ур-е
у=3-4х х=0,5 х=0,5
6х-2(3-4х)=1 у=3-4*0,5 у=1
6х-6+8х=1
14х=7
х=0,5
Похожие вопросы
Предмет: География,
автор: Аноним
Предмет: География,
автор: kichi775
Предмет: Литература,
автор: skvlr
Предмет: Математика,
автор: Аня20031099
Предмет: Биология,
автор: blackangel665